If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+48=4
We move all terms to the left:
2x+48-(4)=0
We add all the numbers together, and all the variables
2x+44=0
We move all terms containing x to the left, all other terms to the right
2x=-44
x=-44/2
x=-22
| =2.3x+17 | | 5/6x-2=2/3+1 | | -6(8+4n)=3(1-7n) | | 6(1+7v)=6(v+1) | | 4x-23=49 | | r=–5(2r+11) | | 3x−8=−2 | | .19x+5.95=18.83 | | 6-8-2c=-16 | | 4(x+5)+6x=10x-20 | | s=2.8=6.59 | | -305m-10=-15 | | -13=-8v+5(v-5) | | 10=14x+3 | | 20=-c | | -3(2x–3)=25–2x | | 52=-8-6n | | 10=14*x+3 | | 7v+5-2(-5v-2)=3(v-3) | | -13=8v+5(v-5) | | 8+x/6=12 | | 3s-22=35 | | 7v+5-2(-5v-2)=3(v-3 | | 1-y=228 | | 3x-8(x-5)=7+4x+20 | | 1=0.75x-0.5 | | 3s−22=35 | | 10x3xX=10x | | x−4(x+13)=26 | | 4(p-6)=20 | | 0.03x=42 | | (8x-3)=(4x+9) |